Development and impact of formal long-distance footpaths in Great Britain - Henshaw, Robin S. (University of Edinburgh, 1984)
This study examines long-distance routes, formal rights of way designed to allow primarily walkers to make extended journeys through attractive areas of British countryside. It traces the idea of the desirability of cross-country footpaths, from its origin in the Romantic Era, through the campaigns fornational parks and freer access to the uplands, to its embodiment in the Pennine Way proposal, and thence through official reports to its incorporation in legislation in 1949. Thereafter, attention is focused on the National Parks Commission, whose statutory responsibility it was to plan long-distance routes, and then the Countryside Commission to what is recognised as the conclusion of the programme for new routes in England and Wales. The Countryside Commission for Scotland's programme for long-distance routes is examined from 1967 when legislation allowed the facility to be created in Scotland. In tracing the hi story of the idea and documenting developments, policies and programmes for Implementing proposals for long-distance routes, specific aspects examined include the cyclical nature of development of the idea, strengths and weaknesses of the legislation, difficulties translating ideas to reality and the selection of specific routes. In addition, ideas tested and confirmed include the fact that the history of long-distance footpaths reflects that of the 20th Century amenity movement in general, that enthusiastic and imaginative individuals in influential positions were of singular importance to the development of the idea and that long-distance routes have attracted attention and interest of- the public, Parliament, the media and user-groups disproportionate to their likely use or physical or economic impact: a distinction is drawn between the .symbolic importance of the idea and the reality of implementation.
The development and impact of formal long-distance footpaths in Great Britain
Keywords: Sports; Recreation; Tourism